A study on the adoption intention of cold chain prepared Dishes based on consumer orientation mentality - Luo, Feng; Shang , Wei; Gan , Junwei (Universitas Ahmad Dahlan, 2023)
Background: Cold chain prepared dishes, as a new type of food with low temperature and dual attributes, have attracted more and more attention from consumers. From the perspective of consumers' brand positioning mentality, this study integrated the brand, quality and other attributes of cold chain prepared vegetables, and studied the positioning mentality and adoption behavior of Chinese consumers In this study, three cold-chain prefabricated dishes,